Enterprise Supply Chain Information Technologies: A Systematic Review - Llanos Sánchez, Luis Miguel (2025)
Technological strategies within the framework of globalisation have changed in a correlational and daily way in companies, business and society, having as a priority to migrate towards information technologies (IT) that are essential in supply chain management (SCM), leading to a cultural, political and economic change; the purpose of the research is to identify and describe the relevant IT used in SCM, and to establish what are the key IT that are applied in the supply chain in the business sector today, using the PRISMA methodology. The impact caused by different IT such as artificial intelligence (AI), machine learning (ML), blockchain (BC), internet of things (IoT), robotic process automation (RPA); are positive and quantitative improvements in processing times of large volumes of information, prediction of market niches, resilience, customer satisfaction, it is concluded that IT does not replace the worker if it is not designed to enhance their skills in critical judgment, decision making; Despite the benefits, there are barriers to IT implementation, depending on the economy in underdeveloped countries, high cost of implementation, lack of adequate infrastructure, change in cultural paradigms.